Synthesis of evasive maneuver control of unmanned aerial vehicle for terminal restrictions - N. Y. Polovinchuk; S. V. Ivanov; L. I. Kotelnitskaya (Advanced Engineering Research, 2018)
Introduction. The solution to the problem of development of suboptimal evasive strategy of unmanned aerial vehicle (UAV) under the conditions of uncertainty of the current motion characteristics, and the future behavior strategy of the interdictor is considered. The FV (flying vehicle) control is organized with maximum efficiency. Herewith, the maneuvering FV trajectory must satisfy the requirements of optimality for some given functions of the phase variables at the final time and the conditions of its path through a specified terminal area space. The initial conditions and the dynamic facilities of the evading and opposing FV at the initial time are assumed to be known. The evading FV control is developed by its onboard guidance and navigation system in real time on nonlinear position feedback control. The work objective is to build an algorithm for solving the problem of synthesis of terminal optimal control of motion of center of mass of highspeed UAV that allows searching for the optimal control in function of the current coordinates of the object. Consideration of the problem in this formulation distinguishes it from the classical conflict tasks on the prosecution to be solved with the involvement of the theory of differential games, and demands computationally efficient solution methods. Materials and Methods. For the UAV operating under the conditions of violent disturbances, the most effective hard constraints on the phase variables and control are the so-called methods of optimal terminal control that implement adaptive algorithms with projection. Therefore, the solution to the formulated problem can be obtained precisely with the use of their ideology. Research Results. A new method of piecewise-software terminal control of the UAV motion is developed. It differs from the known ones in that it is based on the procedure of searching a control strategy upon the best guaranteed result with the terminal restrictions. A methodology for calculating the management strategy for the FV evasive maneuver in a slow loop of the terminal control system is worked out. It is characterized in that instead of the forecast procedure in speed-up time and calculation of residuals, the conversion of a boundary value problem to a one-point task of integration of the ordinary differential equations system with account for the occurrence of non-zero terminal member in the cost functional, is used. Discussion and Conclusions. Despite the fact that the development of a suboptimal guidance strategy in the terminal area of the evading FV is not in the form of synthesis, the control software adapts to the current conditions. This is achieved through the iterative procedures of regular recalculation of terminal conditions that are equivalent to the periodic circuit feedback. Thus, the evading FV is brought to a specified terminal area through software, while evading an interdictor is developed as synthesis. Limitations to the method are the terms that the movement model of the opposing FV is known, and it forms a natural control of the evader intercept.